Physical load on the cardiovascular system in different work tasks. - Ilmarinen, Juhani (Scandinavian Journal of Work, Environment & Health, 1984)
This review of the cardiovascular load at work is based on the concept of stress and strain in dynamic work. The relationship between oxygen consumption (VO2) and heart rate (HR) and work load and the effects of intervening variables are described. The relationship between relative aerobic strain (RAS) and HR is shown to be dependent on the type and combination of muscular work. Significant differences in cumulative HR curves over 8-h shifts have been detected between the profile groups "producing muscle forces" or "coordinating motor functions" and others; the HR remained above the level of 110 beats X min-1 for about 50, 30, and 5% of the shift time, respectively. VO2, HR, and RAS are described in more detail during tasks in milk delivery, mail delivery, and logging, during tasks in the construction and steel industries, and during tasks in the municipal sector. Special attention is paid to work tasks in which the load on the cardiovascular system is above the "acceptable" level. Peak loads which increase strain to the maximal RAS level are described. The change in RAS with ageing is shown to increase in work tasks which include the production of muscle forces and the coordination of motor functions.